1985
DOI: 10.1149/1.2113590
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Active Layer Composition on the Service Life of  ( SnO2   and RuO2 )  ‐ Coated Ti Electrodes in Sulfuric Acid Solution

Abstract: technique has been published for either electroplating or nonelectrolytic plating palladium on zirconium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 0 publications
1
38
1
Order By: Relevance
“…Figure 3 shows that no significant Ru peak displacement was found, and thus no solid solution is formed, contrary to [10]. …”
Section: Mixed Coatingsmentioning
confidence: 97%
See 2 more Smart Citations
“…Figure 3 shows that no significant Ru peak displacement was found, and thus no solid solution is formed, contrary to [10]. …”
Section: Mixed Coatingsmentioning
confidence: 97%
“…As an example, the indium-tin oxide thin films prepared by thermal decomposition, show a minimum in the electrical resistivity for a certain painting solution composition [13]: because of probable Sn losses, this is most likely to be different from the real In-Sn ratio obtained in the annealed coating. Another typical example is the RuO2-SnO2 coating for which a maximum of service life was obtained with a painting solution composition of 30mo1% Ru-70 mol % Sn which was explained by the formation of an RuSn206 compound [10].…”
Section: Mixed Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…This may occur due to the pores in the layer and the rapid evolution of gas on the surface, inducing the separation of weakly bound parts of the active layer [28] [31] [32].…”
Section: Electrochemical Characterizationsmentioning
confidence: 99%
“…However, RuO 2 is not stable in acidic environments, and the O 2 evolution overpotential increases with time [6,7]. Several researchers have reported that the electrochemical stability of DSAs can be significantly improved by incorporating other components into RuO 2 [8][9][10]. In spite of significant improvement in electrochemical stability by introducing various components, the durability of RuO 2 -based DSAs is still insufficient for industrial applications.…”
Section: Introductionmentioning
confidence: 99%